Sweet vernal grasses (Anthoxanthum) colonized African mountains along two fronts in the Late Pliocene, followed by secondary contact, polyploidization and local extinction in the Pleistocene. Issue 13 (3rd May 2017) - Tusiime, Felly Mugizi; Gizaw, Abel; Wondimu, Tigist; Masao, Catherine Aloyce; Abdi, Ahmed Abdikadir; Muwanika, Vincent; Trávníček, Pavel; Nemomissa, Sileshi; Popp, Magnus; Eilu, Gerald; Brochmann, Christian; Pimentel, Manuel
Abstract: High tropical mountains harbour remarkable and fragmented biodiversity thought to a large degree to have been shaped by multiple dispersals of cold‐adapted lineages from remote areas. Few dated phylogenetic/phylogeographic analyses are however available. Here, we address the hypotheses that the sub‐Saharan African sweet vernal grasses have a dual colonization history and that lineages of independent origins have established secondary contact. We carried out rangewide sampling across the eastern African high mountains, inferred dated phylogenies from nuclear ribosomal and plastid DNA using Bayesian methods, and performed flow cytometry and AFLP (amplified fragment length polymorphism) analyses. We inferred a single Late Pliocene western Eurasian origin of the eastern African taxa, whose high‐ploid populations in one mountain group formed a distinct phylogeographic group and carried plastids that diverged from those of the currently allopatric southern African lineage in the Mid‐ to Late Pleistocene. We show that Anthoxanthum has an intriguing history in sub‐Saharan Africa, including Late Pliocene colonization from southeast and north, followed by secondary contact, hybridization, allopolyploidization and local extinction during one of the last glacial cycles. Our results add to a growing body of evidence showing that isolated tropical high mountain habitats have a dynamic recent history involving niche conservatism and recruitment from remote sources, repeated dispersals, diversification, hybridization and local extinction.